2016
DOI: 10.1155/2016/1354186
|View full text |Cite
|
Sign up to set email alerts
|

Chairside Fabrication of an All-Ceramic Partial Crown Using a Zirconia-Reinforced Lithium Silicate Ceramic

Abstract: The chairside fabrication of a monolithic partial crown using a zirconia-reinforced lithium silicate (ZLS) ceramic is described. The fully digitized model-free workflow in a dental practice is possible due to the use of a powder-free intraoral scanner and the computer-aided design/computer-assisted manufacturing (CAD/CAM) of the restorations. The innovative ZLS material offers a singular combination of fracture strength (>370 Mpa), optimum polishing characteristics, and excellent optical properties. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 11 publications
0
25
0
3
Order By: Relevance
“…These new glass-ceramics were designed to contain lithium silicate as the main crystalline phase in a vitreous matrix reinforced with zirconium dioxide crystals (~10%). 48 When this material goes through the crystallization process, the nucleated lithium silicate crystals achieve a mean size (0.5 to 1 μm) that is up to 6 times smaller than that observed for lithium disilicate crystals present in lithium disilicate glass-ceramics. 49 The formation of a smaller and finer crystalline phase occurs due to the presence of zirconia particles in the material, which acts as an additive influencing the crystallization by hindering crystal growth.…”
Section: New Glass-ceramicsmentioning
confidence: 94%
See 1 more Smart Citation
“…These new glass-ceramics were designed to contain lithium silicate as the main crystalline phase in a vitreous matrix reinforced with zirconium dioxide crystals (~10%). 48 When this material goes through the crystallization process, the nucleated lithium silicate crystals achieve a mean size (0.5 to 1 μm) that is up to 6 times smaller than that observed for lithium disilicate crystals present in lithium disilicate glass-ceramics. 49 The formation of a smaller and finer crystalline phase occurs due to the presence of zirconia particles in the material, which acts as an additive influencing the crystallization by hindering crystal growth.…”
Section: New Glass-ceramicsmentioning
confidence: 94%
“…52 These novel zirconia-reinforced lithium silicate glass-ceramics have good mechanical properties associated with an excellent esthetic quality, thus being a valid alterative to lithium disilicate materials for prosthetic rehabilitations with high aesthetic demand. The main advantage of these materials is their timesaving ability for the production of dental restorations, since they are faster to be milled in CAD-CAM machines than lithium disilicate glass-ceramics 53 and are already offered in their fully crystallized state (CELTRA Duo, Dentisply-Sirona, Bensheim, Germany) no furnace need) or need a very short crystallization cycle (Suprinity, Bad Sachingen, Germany). A particular advantage of the lithium silicate ceramic over the lithium disilicate version is the superior polishability due to the smaller crystal sizes in the microstructure.…”
Section: New Glass-ceramicsmentioning
confidence: 99%
“…The 0.4 mm thickness of the material followed the manufacturer's recommendation of minimum thickness for both Suprinity and E-max that can produce good esthetics on teeth with minimal discoloration. It is also considered the thickness of choice for veneers with an acceptable color of the core [5,27,28]. A 0.5 mm thick material is indicated in cases with minimum veneer preparation and acceptable color of the underlying structure.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, data regarding the clinical performance of all‐ceramic restorations remain sparse and are limited to case reports or clinical studies with limited observational periods of less than 2 years …”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Nevertheless, data regarding the clinical performance of allceramic restorations remain sparse and are limited to case reports or clinical studies with limited observational periods of less than 2 years. [20][21][22] Based on the findings of the available clinical studies, the second most common reason for the failure of a CCPC is the debonding of the restorations. Numerous clinical studies have demonstrated a significant effect of the cementation technique on the survival and success rates of CCPCs.…”
Section: Introductionmentioning
confidence: 99%